Blended polymer as composite insulating layers for organic field effect transistor. (March 2022) - Sun, Qiang; Zhu, Yangyang; Han, Di; Wang, Chenxue; Zhang, Yiqun; Liu, Chang; Wang, Lu; Wang, Lijuan
Highlights: Blended polymer insulting layers were prepared by spin-coating. The threshold voltage of the organic field effect transistor is reduced to -14.7 V. The influence mechanism of blended polymer insulating layers is proposed. Abstract: Organic field effect transistors based on blended polymer insulators were fabricated. The effects of polystyrene (PS), poly (vinyldifluoride) (PVDF) and poly (vinylphenyl) (PVP) blended with poly (methylmethacrylate) (PMMA) on the properties of insulating layers were studied. The PMMA:PS films have spherical grains, the PMMA:PVP films exhibit porous pit morphology, and the PMMA:PVDF films still show plane morphology. The morphology of insulating layers can affect the crystallization of organic semiconductors. Meanwhile, the performance of OFET devices indicates that polymer doping decreases the threshold voltage of devices. When the mass ratio of PMMA:PVDF is 10:5, the threshold voltage of OFET devices is about −14.7 V, which is significant lower than that of pure PMMA devices. This is attributed to the larger capacitance and lower roughness of the insulating layers. Therefore, it is a convenient and effective method to optimize the threshold voltage of OFET devices by applying blended polymer insulating layers.